A critical study of contractual liability - عجيل طارق طارق (Journal of Legal Sciences, 2020)
The existence of contractual responsibility, together with civil liability, provoked a profound disagreement in jurisprudence that amounted to a claim to renounce the traditional division between the two responsibilities, and to adhere to uniform rules governing civil liability provisions. These calls have increased and culminated in the writings of the scholar Philip Remy, who explicitly called to the abolition of contractual responsibility, therefore, this research is an attempt to review the modern doctrinal views that denied the existence of contractual responsibility as an independent system Beside civil liability, and to demonstrate the validity to benefit from them in the development of our legislative systems and God conciliator.